Private Values of Risk Tradeoffs at Superfund Sites: Housing Market Evidence on Learning about Risk - Gayer, Ted; Hamilton, James T.; Viscusi, W. Kip (The Review of Economics and Statistics, 2000)
This paper incorporates a Bayesian learning model into a hedonic framework to estimate the value that residents place on avoiding cancer risks from hazardous-waste sites. We show that residents are willing to pay to avoid cancer risks from Superfund sites before the U.S. Environmental Protection Agency (EPA) releases its assessment (known as the Remedial Investigation) of the site. Residents' willingness to pay to avoid risks actually decreases after the release of the Remedial Investigation, suggesting that the information lowers the perceived levels of risk. This estimated willingness to pay implies a statistical value of cancer similar to the value-of-life estimates in labor market studies.